2019
DOI: 10.3390/ijms20225656
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in ROS-Responsive Cell Sheet Techniques for Tissue Engineering

Abstract: Cell sheet engineering has evolved rapidly in recent years as a new approach for cell-based therapy. Cell sheet harvest technology is important for producing viable, transplantable cell sheets and applying them to tissue engineering. To date, most cell sheet studies use thermo-responsive systems to detach cell sheets. However, other approaches have been reported. This review provides the progress in cell sheet detachment techniques, particularly reactive oxygen species (ROS)-responsive strategies. Therefore, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…85 While this strategy can effectively release cell sheets for downstream utilization, the high levels of ROS that are generated have the potential to harm cells and damage DNA, inducing apoptotic cell death as the duration or intensity of exposure is increased. 71 NIR Light (808 nm)-Induced CST Na et al 99 constructed cell sheets using a near-infrared (NIR) light-based approach that is promising owing to the ability of NIR light to penetrate tissues while remaining safer than visible or ultraviolet light at a given intensity level (Figure 2D). These researchers were able to separate cell sheets in 5 minutes owing to the poly(3,4-ethylenedioxythiophene) (PEDOT) substrate's strong photothermal efficiency in response to NIR light diffraction through a micropatterned optical lens.…”
Section: Photo-responsive Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…85 While this strategy can effectively release cell sheets for downstream utilization, the high levels of ROS that are generated have the potential to harm cells and damage DNA, inducing apoptotic cell death as the duration or intensity of exposure is increased. 71 NIR Light (808 nm)-Induced CST Na et al 99 constructed cell sheets using a near-infrared (NIR) light-based approach that is promising owing to the ability of NIR light to penetrate tissues while remaining safer than visible or ultraviolet light at a given intensity level (Figure 2D). These researchers were able to separate cell sheets in 5 minutes owing to the poly(3,4-ethylenedioxythiophene) (PEDOT) substrate's strong photothermal efficiency in response to NIR light diffraction through a micropatterned optical lens.…”
Section: Photo-responsive Systemsmentioning
confidence: 99%
“…In addition, the resultant cell sheets do not detach in the form of cellular monolayers, instead forming cellular aggregate clumps. 71,86 pH-Responsive Systems Guillaume-Gentil et al 91 suggested a pH-responsive culturing technique for the manufacture of cell sheets. Layer-bylayer deposition of cationic poly (allylamine hydrochloride) and anionic poly (styrene sulfonate) onto conductive electrodes made of indium tin oxide was used in this method, and cells were then seeded onto the resulting surface.…”
Section: Magnetic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a smart polymer, PIPAAm was used for the first time to form a cell sheet, which is now commercially available (Sudo et al, 2018 -Gentil, Gabi, et al, 2011;Guillaume-Gentil, Semenov, et al, 2011;Z. Jia, Guo, et al, 2018;M.-A. Koo et al, 2019;Y.…”
Section: General Overview Of Cell Sheet Strategiesmentioning
confidence: 99%
“…However, a variety of stimuli‐responsive polymers and various methods, including temperature‐responsive, photo‐responsive, chemical‐responsive, ROS‐responsive, pH‐responsive, electric field‐responsive, magnetic field‐responsive, and mechanical‐responsive methods, have been proposed for the fabrication of cell sheets (Guillaume‐Gentil, Gabi, et al, 2011; Guillaume‐Gentil, Semenov, et al, 2011; Z. Jia, Guo, et al, 2018; M.‐A. Koo et al, 2019; Y. B. Lee et al, 2018; Noh et al, 2019; Park et al, 2018; Y. Zhu et al, 2018).…”
Section: Cell Sheet Engineeringmentioning
confidence: 99%